Analisis Critical Success Factor Kinerja Proyek Preservasi Jalan Nasional dengan Skema Long Segment: Pelaksanaan di Provinsi Sumatera Utara - Masista Marpaung; M. Ridwan Anas; Gina Cynthia Raphita Hasibuan (Syntax Idea)
A construction project is a form of activity that takes place within a certain period of time and with certain resources to achieve results in the form of buildings or infrastructure. Problems that occur in a construction project are determined by the suitability of time, cost, and quality agreed in the contract documents. The road handling project is one of the areas of construction projections that are also fighting for the project. The road maintenance program in Indonesia is implemented by the Ministry of Public Works and Public Housing in the form of a preservation project with a long segment scheme. The long segment scheme has performance indicators that can assess the performance of road preservation projects so that the success of road preservation projects can be measured. This underlies this research to analyze the Critical Success Factor (CSF) on the success of road preservation projects. The Partial Least Square – Structural Equation Modeling (PLS – SEM) analysis method was used in this study to analyze the CSF performance of a road preservation project with a long segment scheme. The results of the analysis show that the Critical Success Factor that has an impact on the success of the road preservation project with the long segment scheme is the standard quality test factor with a value of 0.371 having the greatest impact. Overall, the CSF factors of the performance of the road preservation project with the long segment scheme have quite an effect (moderate) on the success of the project in the performance indicator slogan, namely with a proportion value of 47.5%. In conclusion, overall the Critical Success Factor elements of road preservation project performance with a long segment scheme are quite influential on project success in the performance indicator slogan, namely with a proportion value of 47.5%.